(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The purpose of these brief considerations is to identify some theoretical starting points relating to the state of emergency. In this regard, after a general recognition of the category, the relationship between the constitutional state and the state of emergency will be highlighted, also in contrast with the authoritarian state; therefore, the article will concentrate on the unstable border between the state of emergency and the state of exception, examining, at the end, the emergency situation caused by the CoViD-19 in the theoretical frame mentioned above.